Building a Website Based Gemstone Authenticity Certificate Information System - Arga Pradana; Suprianto (Procedia of Engineering and Life Science, 2021)
In practice, the Gems Identification Laboratory (GIL) process of recording gemstone authenticity certificates is still manually and data only stored on hard disk, making it easier to create fake certificate. because the certificate can be printed by anyone, and the certificate code cannot be verified by the gemstone buyer or user, when the user buys gemstones outside the area from the Lab location. User must also send a short message to the admin to verify the authenticity of the certificate document printed by the Lab. The method used in this study uses observational data collection. The system was tested using XAMPP software. The results of this study are a website based gemstone authenticity certificate information system that can make it easier for users to check certificates anywhere by using a code that will be traced on the website without having to come to the Lab. Lab admins can also input and save certificate data in the admin menu.